Implementing Mindfulness: Practice as the Home of Understanding - Nelson, Donald L. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2012)
The practice of mindfulness is a contemplative practice that has been implemented in educational settings as well as in various models of treatment for stress and other conditions. This paper examines how Western scientific psychology has participated in this implementation and the dangers to the practice and concepts of mindfulness inherent in shifting a practice from the cultural and philosophic ground in which it developed to another ground and another discourse. Some caveats for implementing contemplative practices are considered.